Mosque Financial Management ( Study Cases At Mosques In The District Herlang Regency Bulukumba ) - Suarni, Agusdiwana; Nurlina, Nurlina; Yulianti, Irna (Jurnal Ar-Ribh, 2023)
Study This aim For investigate practice management financial funds for mosques in the district Herlang , Regency Bulukumba . Study This use method qualitative descriptive that combines observation , interviews , and documentation as tool data collection . Data sources used in study This consists from primary data and secondary data . Research results indicated that fund management at the Nurul Yaqin Mosque , Nurul Hijad , Nurul Amin, and Babul Khaer Mosque based on principles management finance , incl planning , implementation , and evaluation . Management of mosque funds involves a number of aspect important , like system receiving funds, managing funds, and reporting funds. The potential funds managed by the mosque make it possible become A source well-being for public local area and contribute to the prosperity of the mosque yourself . In context this , practice management Good finances in the Mosque are very important For ensure that funds are received and managed with efficient and transparent . Research results This can give valuable insight _ about How management finance can improved in context management of mosque funds in this region.